Przeszłość południowokresowej rezydencji w Psarach utrwalona w archiwum ludzkiej pamięci i wybranych, współczesnych źródłach pisanych (refleksje filologiczno-lingwokulturologiczne) = The past of the Polish southeastern borderlands residence in Psary preserved in an archive of human memory and selected contemporary records (philological-linguaculturological reflections) - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The text is focused on an attempt at a philological-linguaculturological reconstruction of Psary (manor-mansion-residence), southeastern borderlands that, with the help of the various kinds of memorializing means stored in an archive of human memory, has been preserved in complementary works: 1) borderland encyclopedia and 2) borderland guide - sources presenting the factographic perspective - and 3) borderland memories by Anna Rey Konstantynowa Potocka - a text represent?ing the emotional perspective.
Keywords: przeszłość; pamięć; archiwum ludzkiej pamięci; faktografia; emocje; Kresy; past; memorializing means; archive of human memory; factography; emotions; Polish borderlands